Sarcomatous transformation of IDH-mutant astrocytoma matching to methylation class oligosarcoma following embolization, a case report - Ryan Landvater; Arushi Tripathy; Edwin Nieblas-Bedolla; Lina Shao; Kyle Conway; Wajd Al-Holou; Sean P. Ferris (Acta Neuropathologica Communications)
Abstract The mesenchymal transformations of infiltrating gliomas are uncommon events. This is particularly true of IDH-mutant astrocytomas and oligodendrogliomas, in which mesenchymal transformation is exceedingly rare. oligosarcoma is a newly recognized methylation class (MC) that represents transformed 1p/19q co-deleted oligodendrogliomas, but recent studies indicate it may be non-specific. Herein we report the diffuse sarcomatous transformation of a multifocal recurrent astrocytoma from a precursor IDH-mutant astrocytoma, CNS WHO grade 3, in a young patient following embolization therapy and matching to MC oligosarcoma. The sarcomatous recurrence and original tumor showed identical 17q breakpoints with loss of heterozygosity of TP53. Both lack the defining 1p/19q co-deletion or copy-neutral heterozygosity of an oligodendroglioma and oligosarcoma. The findings in this case report both contribute to the apparent heterogeneity of the novel MC oligosarcoma and describe a second reported mesenchymal transformation of an IDH-mutant astrocytoma.